RANCANG BANGUN LOKER PENGAMAN PENITIPAN OTOMATIS MENGGUNAKAN SISTEM SPECIAL CODE - Nafis Syaefullah; Shela Hermawan; Surojo Surojo; Valentin Vina Ratnapuri (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Conventional storage lockers had security limitations because they relied on physical keys that could be lost, damaged, or misused. This study aimed to design and implement an automatic locker security system using a special code method for user authentication. The system was developed using an ESP32 integrated with a keypad, a 16×2 LCD, a magnetic reed switch, a relay, a solenoid door lock, a buzzer, LEDs, and the Blynk application for monitoring and access management. The research method consisted of system planning, hardware and software design, implementation, and functional testing of all system components. The testing results showed that the proposed system successfully performed access code verification, automatic locking and unlocking, password modification, forced-entry detection, and system recovery. Implementing the special code method improved locker security, simplified user operations, and enhanced the efficiency of storing and retrieving belongings compared with conventional locker systems.